HYPERAESTHETIC INTERTEXTUAL PRACTICE IN A PICTORIAL TEXT FEATURING IRACEMA: A LEGEND FROM CEARÁ AS A HYPOTEXT - Cabral Nobre , Kennedy; Oliveira de Sousa, Antonia Karoline; Oliveira de Sousa, Antonia Karine (Revista de Letras, 2025)
This article discusses the phenomenon of intertextuality present in a pictorial text derived from a literary work, more specifically, a hyperaesthetic intertextual practice (PIH), the canvas Iracema (1924), which transforms the literary work Iracema: legend from Ceará, by José de Alencar, into a painting. Therefore, the aim of this paper is to analyze the linguistic, plastic and iconic messages, as well as the intertextual parameters found in the pictorial piece, based on the theoretical-methodological framework for PIH analysis adapted by Sousa (forthcoming) from the proposals of Nobre (2014) and Silva (2016). To this end, we used the works of Genette (2010), Nobre (2014), Silva (2016) and Sousa (forthcoming) as the theoretical and methodological basis for our study. Furthermore, the analysis revealed that the screen Iracema (2024) adapts a specific passage from the source text. This recognition is made possible by reading the linguistic/discursive, plastic and iconic elements present in the work and by maintaining the referents of the hypotextor Sousa (to leave) based on the proposals of Nobre (2014) and Silva (2016). Concerning the intertextual parameters, the functional parameter shows a relationship of capture for convergence, since the new text does not subvert the original text; regarding the hierarchy of the constitutional parameter, the compositional parameter shows a relationship of derivation, since the hypertext is formed entirely by the hypotext and the hypotext is not just a fragment in a larger text; in the formal parameter, we have an adaptation of the original work; in the referential parameter, we see a greater degree of explicitness, especially as the title of the new text is made up of the name of the title character of the original work. Finally, with regard to the stylistic parameter, the hypertext was produced under the influence of an avant-garde school.